Analisa Unsur-unsur Tafsir Jalalain sebagai Teks Hipogram dalam Tafisr Al-Ibriz: Kajian Intertekstual Julia Kristeva QS. Maryam: 1-15 - Aaviy Lailaa Kholily (Faculty of Ushuludin Institute of Al-Qur’an Science (IIQ) An Nur Yogyakarta Indonesia, 2021)
This paper will try to examine al-Ibriz's interpretation and Jalalain's interpretation with an intertextual approach, but within the scope of the researcher, the researcher will only try to examine the Surah Maryam verses 1 to 15 with the formulation of the problem, first: What are the elements of Jalalain's interpretation contained in the interpretation al-Ibriz on the interpretation of the letter Maryam verses 1 to 15? Second: What are the principles used by K.H Bisyri Mustafa in processing Jalalain's interpretation as his hypogram text on the interpretation of Maryam verses 1 to 15? From the results of the analysis, the researchers found the elements of Jalalain's interpretation contained in al-Ibriz contained in verses 1,3,5,6,7,12, and 13. As for the principles used to process the hypogram, several principles were found, namely the principle of transformation , haplology, expansion and parallel.